Optimal extracellular production of recombinant Bacillus circulans β-galactosidase in Escherichia coli BL21(DE3). (February 2017) - Duan, Xuguo; Hu, Shubing; Qi, Xuhui; Gu, Zhengbiao; Wu, Jing
Graphical abstract: Highlights: β-Galactosidase production conditions (induction time, temperature, concentration of lactose, etc) were optimized in a 3-L fermentor. The highest extracellular enzyme activity was 18.5-fold that of the original extracellular enzyme activity in 3-L fermenter. Peak extracellular β-galactosidase activity reached 220.0 U mL −1 . Abstract: The β-galactosidase-catalyzed conversion of lactose to galactooligosaccharides offers an attractive approach for the efficient production of galactooligosaccharides. In this study, the β-galactosidase from Bacillus circulans was overexpressed in Escherichia coli BL21(DE3), and its extracellular secretion was characterized and optimized. Using initial parameters determined during fermentation tests in shake-flasks, extracellular expression was optimized in a 3-L fermentor. Three key parameters were studied: time of induction initiation, induction temperature, and inducer (lactose) feeding rate. Optimal extracellular β-galactosidase activity was observed when: induction was initiated when the optical density at 600 nm reached 40; (2) expression was induced at 37 °C; and (3) lactose was added at a constant feeding rate of 1.0 g L −1 h −1 . Under optimal conditions, the extracellular activity reached 220.0 U mL −1, which represents 65.0% of the total β-galactosidase activity expressed. This high-level production of soluble β-galactosidase in a semisynthetic medium provides a model for the industrial production of β-galactosidase.